Evaluation of the Effectiveness of Composite Radar Rainfall Estimation Using the Quality Index Technique in Mountainous Terrain with a Weather Radar Network in Northern Thailand - Sukha, Wirongrong; Puttaraksa Mapiam, Punpim (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 30, 2025)
Radar measurements in mountainous regions with complex terrain present significant challenges due to beam blockage. Consequently, rainfall estimation based on data from a single weather radar station may be subject to substantial inaccuracies. The application of composite radar techniques, which integrate data from multiple radar stations, provides a potential approach for improving the accuracy of radar-based rainfall estimation. This study aims to evaluate the effectiveness of composite radar rainfall estimation in mountainous terrain using the quality index technique, considering three key environmental factors: 1) radar beam blockage, 2) radar beam height above the terrain, and 3) distance from the radar station. Data from three weather radar stations—Chiang Rai, Nan, and Phitsanulok—were utilized in the analysis. The effectiveness of radar-derived rainfall estimates was assessed by comparing them against measurements from automatic rain gauge stations for 21 rainfall events recorded during tropical storm Son-Tinh (between June and September 2018). The results indicate that the quality index-based composite radar technique yields superior performance on average compared to single-radar data. When combined with bias correction, the composite method enhances spatial rainfall representation, providing improved quantitative accuracy at all rainfall intensity levels, showing an improvement of approximately 25% compared to pre-correction estimates. This improvement is particularly pronounced in areas affected by beam blockage. Moreover, considering the impact of radar elevation angle adjustments may further enhance the effectiveness of radar-based rainfall estimation in mountainous regions.